Scientific Reasoning Profile on Light Properties in Elementary Students: Profil Penalaran Ilmiah tentang Sifat-Sifat Cahaya pada Siswa Sekolah Dasar - Engel sesilia putri Putri; enik setiyawati (Academia Open, 2025)
General Background: Scientific reasoning is a fundamental component of science learning and a key competency in 21st-century education, particularly in elementary school science. Specific Background: In IPAS learning on light properties, students are expected to observe phenomena, formulate hypotheses, analyze evidence, and draw logical conclusions, yet classroom practices often do not fully facilitate these reasoning processes. Knowledge Gap: Limited empirical descriptions exist regarding elementary students’ scientific reasoning profiles specifically on the topic of light properties within authentic classroom contexts. Aims: This study aims to analyze and describe the scientific reasoning abilities of elementary school students in learning about light properties. Results: The findings indicate varied levels of reasoning across indicators, including observation, classification, hypothesis formulation, and conclusion drawing, with some students demonstrating partial understanding and others showing difficulties in connecting evidence to explanations. Novelty: The study provides a focused qualitative profile of scientific reasoning on light properties using structured observation indicators in an elementary classroom setting. Implications: The results suggest the need for instructional strategies that systematically engage students in inquiry-based and evidence-based learning to strengthen scientific reasoning in IPAS. Keywords: Scientific Reasoning, Light Properties, Elementary Education, IPAS Learning, Qualitative Analysis Key Findings Highlights: Students show uneven mastery across reasoning indicators in science learning Difficulties emerge in linking experimental evidence to logical explanations Structured observation reveals detailed patterns of classroom reasoning processes